2019
DOI: 10.21037/qims.2019.04.09
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors associated with delirium after lumbar spine surgery in elderly patients

Abstract: Background: To prospectively explore the incidence and risk factors for postoperative delirium in elderly patients following lumbar spine surgery.Methods: This prospective study enrolled 148 consecutive patients over the age of 65 who were scheduled to undergo spine surgery. Patients were screened for delirium using the short Confusion Assessment Method (CAM) postoperatively. Patient demographics and relevant medical information were collected. Logistic regression analysis was used to identify the risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…However, diabetes mellitus, history of surgery, and cerebral vascular diseases were not found to be related to developing delirium, which was consistent with the previous meta-analysis [47]. For the cardiovascular comorbidity, the pooled result of 10 studies [8, 11, 15, 23, 26, 30, 31, 34, 43, 45] showed no significance (OR 0.81; 95% CI 0.34–1.29) with low heterogeneity ( I 2 0%) (Figure 4(a)). Only one study found cardiovascular comorbidity as a risk factor for delirium [11].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…However, diabetes mellitus, history of surgery, and cerebral vascular diseases were not found to be related to developing delirium, which was consistent with the previous meta-analysis [47]. For the cardiovascular comorbidity, the pooled result of 10 studies [8, 11, 15, 23, 26, 30, 31, 34, 43, 45] showed no significance (OR 0.81; 95% CI 0.34–1.29) with low heterogeneity ( I 2 0%) (Figure 4(a)). Only one study found cardiovascular comorbidity as a risk factor for delirium [11].…”
Section: Discussionsupporting
confidence: 85%
“…Delirium is thought to be a less transient disorder than previously believed in several studies [8, 11]. In addition, it has been reported that patients with postoperative delirium have a higher mortality rate than in those without it [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ]. In elderly patients after lumbar spine surgery, risk factors associated with delirium were male gender and parkinsonism, and lower baseline Mini-Mental State Examination (MMSE) scores showed a more regular occurrence rate [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis-related complications can be decreased by active/passive limb movement, antithrombotic stockings and early ambulation. Notably, advanced age is one of the main risk factors for postoperative delirium, and the incidence of postoperative delirium after elective lumbar surgery can be as high as 15%, which can lead to nursing di culties and lower compliance with the ERAS protocols [24][25][26].…”
Section: Discussionmentioning
confidence: 99%